2014
DOI: 10.1007/s12013-014-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adenosine A2A Receptor Antagonist Istradefylline as Augmentation for Parkinson’s Disease: A Meta-analysis of Randomized Controlled Trials

Abstract: Adenosine A2A receptor antagonist istradefylline has been approved this year for manufacturing and marketing in Japan. We, therefore, did this meta-analysis to systematically assess the efficacy and safety of istradefylline as augmentation to levodopa in patients with Parkinson's disease (PD). We systematically review the relative randomized controlled trials (RCTs) up to March 2014, which compared istradefylline to placebo for the short course of treatment for PD in adults. The primary outcome was daily OFF t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…K ATP ( Dragicevic et al, 2015 ) and P2X1R ( Gan et al, 2015 ; Navarro et al, 2016 ; Yang Z. et al, 2016 ) in PD have also been reported, perhaps indicating new therapeutic targets. Clinical trials istradefylline, an A 2A R antagonist, have taken place and it may have a beneficial effect in conjunction with commonly used anti-Parkinson’s therapies ( Tao and Liang, 2015 ; Uchida et al, 2015 ; Vorovenci and Antonini, 2015 ), although in a later study, istradefylline was shown to enhance amyloid-β generation and γ-secretase activity ( Lu et al, 2016 ). Oligomerisation kinetics of A 2A and dopamine D 2 R have important implications for PD ( Casadó-Anguera et al, 2016 ; Ferré et al, 2016 ; Guixà-González et al, 2016 ).…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%
“…K ATP ( Dragicevic et al, 2015 ) and P2X1R ( Gan et al, 2015 ; Navarro et al, 2016 ; Yang Z. et al, 2016 ) in PD have also been reported, perhaps indicating new therapeutic targets. Clinical trials istradefylline, an A 2A R antagonist, have taken place and it may have a beneficial effect in conjunction with commonly used anti-Parkinson’s therapies ( Tao and Liang, 2015 ; Uchida et al, 2015 ; Vorovenci and Antonini, 2015 ), although in a later study, istradefylline was shown to enhance amyloid-β generation and γ-secretase activity ( Lu et al, 2016 ). Oligomerisation kinetics of A 2A and dopamine D 2 R have important implications for PD ( Casadó-Anguera et al, 2016 ; Ferré et al, 2016 ; Guixà-González et al, 2016 ).…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%
“…antagonist, have been undertaken and it was suggested that it could be an efficacy and safety augmentation drug added on to levodopa or other existing anti-Parkinson's therapies [35]. Later studies have supported this strategy [36,37].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The A 2A R antagonist istradefylline (KW‐6002, Fig. ) has been approved in Japan as an adjuvant in treatment of PD patients with L‐DOPA (where DOPA is dihydroxyphenylalanine) . It can reduce motor fluctuations (off‐time) during dopamine replacement therapy.…”
Section: Therapeutic Applications Of A2ar Antagonistsmentioning
confidence: 99%